2013
DOI: 10.3390/agronomy3040757
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Applications of Chitin and Its Derivatives in Agriculture to Modify Plant-Microbial Interactions and Improve Crop Yields

Abstract: Abstract:In recent decades, a greater knowledge of chitin chemistry, and the increased availability of chitin-containing waste materials from the seafood industry, have led to the testing and development of chitin-containing products for a wide variety of applications in the agriculture industry. A number of modes of action have been proposed for how chitin and its derivatives can improve crop yield. In addition to direct effects on plant nutrition and plant growth stimulation, chitin-derived products have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(224 citation statements)
references
References 210 publications
1
194
1
6
Order By: Relevance
“…The treatment resulted in a 30% lower number of isolates of pathogenic fungi, including those causing parasitic damping-off, and higher numbers of isolates of bacteria of the genera Bacillus and Pseudomonas, as well as fungi of the genera Aspergillus, Gliocladium, and Trichoderma. The stimulation of growth of these groups of soil microorganisms results from their ability to synthesize chitinases, i.e., the enzymes that determine their resistance to the influence of chitosan [8,21]. Simultaneously, the high chitinolytic activity makes it possible to use the above-mentioned genera of bacteria and fungi for plant production, as plant-growth-promoting rhizobacteria (PGPR) and plant-growth-promoting fungi (PGPF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment resulted in a 30% lower number of isolates of pathogenic fungi, including those causing parasitic damping-off, and higher numbers of isolates of bacteria of the genera Bacillus and Pseudomonas, as well as fungi of the genera Aspergillus, Gliocladium, and Trichoderma. The stimulation of growth of these groups of soil microorganisms results from their ability to synthesize chitinases, i.e., the enzymes that determine their resistance to the influence of chitosan [8,21]. Simultaneously, the high chitinolytic activity makes it possible to use the above-mentioned genera of bacteria and fungi for plant production, as plant-growth-promoting rhizobacteria (PGPR) and plant-growth-promoting fungi (PGPF).…”
Section: Discussionmentioning
confidence: 99%
“…Research on chitosan as a plant protection product and growth stimulant has so far concerned various herbaceous crop plants, while only few studies have focused on woody plants, including forest trees [8,21,30]. This study aimed to assess the effectiveness of chitosan applied in the form of Beta-chikol as a seed treatment agent and foliar spray to protect Scots pine (Pinus sylvestris L.) against parasitic damping-off and Lophodermium needle cast in a forest nursery (in the ground).…”
mentioning
confidence: 99%
“…Chitosan is obtained from deacetylation of chitin, a compound rich in the exoskeleton of arthropods, beaks of cephalopods (e.g. octopuses, squid, and cuttlefish), and cell walls and membranes of various microbes including fungi (Sharp, 2013). Chitosan is primarily composed of glucosamine and N-acetyl glucosamine residues with 1,4-β-linkage (Rinaudo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that chitosan is not only an antimicrobial agent but also an effective elicitor of plant systemic acquired resistance to pathogens (Sharp et al, 2013;Katiyar et al, 2014;Xing et al, 2014), enhancer and regulator of plant growth, development and yield (Gornik et al, 2008;Cabrera et al, 2013;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%